New Structural Economics : A Framework for Rethinking Development and Policy - Lin, Justin Yifu (Washington, DC: World Bank, 2012)
The new structural economics argues that the best way to upgrade a country's endowment structure is to develop its industries at any specific time according to the comparative advantages determined by its given endowment structure at that time. The economy will be most competitive, the economic surplus will be the largest, and the capital accumulation and the upgrading of factor endowment structure will be the fastest possible. The 'New Structural Economics' presented in this book is an attempt to set out this third wave of development thinking. Taking into account the lessons learned from the growth successes and failures of the last decades, it advances a neoclassical approach to study the determinants and dynamics of economic structure. It postulates that the economic structure of an economy is endogenous to its factor endowment structure and that sustained economic development is driven by changes in factor endowments and continuous technological innovation. The paper also discusses binding constraints to growth in each of these industries' value chains as well as mechanisms through which governance-related issues in the implementation of industrial policy could be addressed.